A Study in Aerodynamic Optimization of UAV Helicopter Rotor- Blades Planform in Vertical Motion - M F Afthon; M A Moelyadi (Institut Teknologi Bandung, 2020)
According to the objectivity of UAV helicopter, endurance is a valuable performance. To increase the endurance, we need to decrease the helicopter required power. Within the research scope in vertical movement only, 5 parameters of blades planform design were considered as design variables. They are root chord of the blades, taper location, taper ratio, pitch angle, and tip twist angle. Optimization was done using own developed genetic algorithm codes with built-in blade element momentum theory (BEMT) as a performance calculator. It was chosen due to its ability to estimate rotor performance quickly. Several CFD simulation were done to reduce the error of blade element momentum theory calculation. Using constant adjustment methods, BEMT can predict thrust and power with a difference with respect to CFD of 3.8% and 8.2% respectively. The optimization result gives the optimum blades design with improving almost 11% in efficiency which came out from 9.4% reduction in power required which is good for helicopter performance.